Evaluation of the adhesive properties of vanillin-derived polyhydroxy urethanes - Ghuge, Gorakh Hiraman; Kambikanam, Karthika Vayalachery; Nair, Kiran Sukumaran (Journal of Applied Polymer Science, 2023)
Poly(hydroxy urethanes) (PHUs) have been considered attractive and safer variants of conventional polyurethanes (PUs). To improve the prerequisites of green and sustainable chemistry herein, we propose the synthesis and utilization of cyclic carbonate monomers majorly derived from vanillin, a lignin derivative, and CO2 for the development of PHUs. Kinetic evaluation on the polymerization temperature ascertained 80 degrees C as the optimum condition for PHU synthesis. The structural evaluation of PHUs was carried out by various spectroscopic techniques, such as FTIR, (HNMR)-H-1, and C-13-NMR, molar masses were determined by gel permeation chromatography (Mn varied between 2500 and 11,100 g/mol), and thermal properties evaluated by differential scanning calorimeter (Tg in the ranges of 28-42 degrees C), and thermogravimetric analysis (stable above 180 degrees C). Since the PHUs are enriched with pendant hydroxyl groups on their backbone which can promote adhesion, lap shear studies on the aluminum substrate exhibited a maximum shear strength of 1.65 +/- 0.37 MPa. This study demonstrates an attractive and environment-friendly pathway for developing novel PHUs network using renewable biobased resources and further explores its applicability as adhesives.
Keywords: adhesive; biobased cyclic dicarbonate; diamines; poly(hydroxyurethane)s; Vanillin

Biobased reusable nonisocyanate polyurethane hot-melt adhesives with potential chemical degradability - Ghuge, Gorakh Hiraman; Torris, Arun; Nair, Kiran Sukumaran (ACS Applied Polymer Materials, 2024)
Hot-melt adhesives (HMAs) derived from renewable resources are always attractive, as they promote less dependence on fossil resources and aid in developing environmentally friendly materials. However, developing sustainable HMAs exhibiting good adhesive performance and biodegradability remains challenging. Herein, reusable biobased HMAs with a high bio content of 88-90%, biodegradability, and tunable adhesive nature were developed as a possible alternative to conventional petroleum-based hot-melt adhesives. Moreover, the structure-property relationship of the product was investigated in detail. By tailoring the monomer composition, NIPU-40 HMA exhibited a good bonding ability with a superior adhesion strength of 6.39 MPa. To the best of our knowledge, this is the highest adhesion strength observed when bonding with an Al substrate among the biobased thermoplastic NIPU-HMAs. Impressively, NIPU-HMAs could display excellent reusability even after three bonding and debonding cycles without a significant drop in the adhesive strength and were found to exhibit good adhesion performance under wet conditions. More importantly, the NIPU-HMAs are prone to degradation under acid-catalyzed conditions. Considering their features, these biobased NIPU thermoplastic hot-melt adhesives offer an opportunity to create environmentally friendly, degradable adhesives that possess excellent adhesive strength and can be reused multiple times.
Keywords: acid degradability; biobased NIPUs; cyclic carbonates; hot meltadhesives; lap shearstrength; spiro-aromatic

Post-functionalizable and reusable biobased polyhydroxyurethane adhesives with pendant furyl groups - Ghuge, Gorakh Hiraman; Nair, Kiran Sukumaran (Reactive & Functional Polymers, 2025)
Polyurethane hot melt adhesives (PU-HMAs) are essential in various industries due to their fast-setting properties, strong adhesion, and versatility across a wide range of substrates. However, conventional fossil-based PUHMAs face significant challenges, including reliance on non-renewable resources, high environmental impact, and the use of hazardous isocyanates, which pose health and safety concerns. To address these issues, this study focuses on developing sustainable, high-performance PHU-HMAs containing pendant furyl groups for metal bonding. A series of adhesives were developed utilizing varying proportions of two biobased dicarbonates derived from lignin and sugar: one featuring a pendant furyl group (BGF-PF-DC) and another without the pendant group (BGF-DC), in conjunction with Priamine 1074. The study comprehensively examined the effects of these formulations on the physio-mechanical, thermal, and adhesive properties. The results demonstrated an impressive renewable carbon content of 89-90 %, high adhesion strength of up to 9.27 MPa on aluminum and 9.43 MPa on stainless steel, excellent underwater adhesion, and outstanding reusability. Furthermore, the postmodifiability of pendant furyl in PHU6-PF100 was evaluated through cross-linking via the Diels-Alder reaction with bismaleimides (BMI). This study also examined the effects of these modifications on both the adhesive performance and thermal characteristics of the modified PHUs. However, the postmodified PHU/BMI network showed a decrease in adhesion but exhibited a higher glass transition temperature and improved adhesion stability at 50 degrees C compared to PHU6-PF100. This study emphasizes the sustainable and high-performance potential of PHU-based hot melt adhesives, establishing them as a viable alternative to traditional isocyanate-based systems. Furthermore, it introduces new opportunities for incorporating Diels-Alder (DA) chemistry into PHU adhesives, which allows for stable adhesion at elevated temperatures and broadens their applicability across various industries. Additionally, this research can serve as a foundation for future studies to investigate thermoreversibility in thermosetting PHUs, potentially expanding their range of applications even further.
Keywords: Biobased polyhydroxyurethanes; Diels-Alder reaction; Hot melt adhesives; Lap shear strength; Pendant furyl

Thrombin immobilized hemocompatible radiopaque polyurethane microspheres for topical blood coagulation - Naik, Sonali S.; Torris, Arun; Ghuge, Gorakh Hiraman; Karthika, V. K.; Joseph, Roy; Nair, Kiran Sukumaran (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH PART A, 2025)
Keywords: ALGINATE MICROSPHERES; ENDOVASCULAR TREATMENT; PRECISE LOCALIZATION